2021
DOI: 10.1038/s41560-021-00887-6
|View full text |Cite
|
Sign up to set email alerts
|

Inequitable access to distributed energy resources due to grid infrastructure limits in California

Abstract: Persistent social disparities in the adoption of distributed energy resources (DERs) have prompted calls for enabling more equitable uptake. However, there are indications that limits inherent to grid infrastructure may hinder DER adoption. In this study we analysed grid limits to new DER integration across California's two largest utility territories. We found that grid limits reduce access to solar photovoltaics to less than half of households served by these two utilities, and may hinder California's electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(34 citation statements)
references
References 42 publications
(75 reference statements)
0
34
0
Order By: Relevance
“…Because home heating and EV charging will create demands for electricity that vary spatially and temporally, estimating distribution grid impacts due to electrification requires spatially and temporally explicit models of electricity consumption. The characteristics of distribution grid infrastructure also vary spatially: research on distribution grid substations (Allen et al 2016, Burillo et al 2018, Sathaye et al 2011 and circuits (Brockway et al 2021) has identified correlations with geography and demographics, including the vulnerability of substations to climate change (Burillo et al 2018) and the ability of distribution circuits to accommodate distributed energy resources (Brockway et al 2021). Investigating the distribution grid impacts of electrification in a spatially and temporally coarse manner, then, is insufficient given the importance of the timing and location of new electric loads as well as the timing and location of the distribution grid's ability to serve them.…”
Section: Residential Electrification Ev Adoption and The Distribution...mentioning
confidence: 99%
“…Because home heating and EV charging will create demands for electricity that vary spatially and temporally, estimating distribution grid impacts due to electrification requires spatially and temporally explicit models of electricity consumption. The characteristics of distribution grid infrastructure also vary spatially: research on distribution grid substations (Allen et al 2016, Burillo et al 2018, Sathaye et al 2011 and circuits (Brockway et al 2021) has identified correlations with geography and demographics, including the vulnerability of substations to climate change (Burillo et al 2018) and the ability of distribution circuits to accommodate distributed energy resources (Brockway et al 2021). Investigating the distribution grid impacts of electrification in a spatially and temporally coarse manner, then, is insufficient given the importance of the timing and location of new electric loads as well as the timing and location of the distribution grid's ability to serve them.…”
Section: Residential Electrification Ev Adoption and The Distribution...mentioning
confidence: 99%
“…Data-driven secondary modeling and screening techniques can help utilities assess customer applications more quickly and with greater certainty. Additionally, screening guidelines based on common distribution network attributes can be used to identify inequities in the grid that prevent customers from benefiting from solar (Brockway, Conde and Callaway 2021).…”
Section: Project Objectivesmentioning
confidence: 99%
“…Debates on low-carbon transitions increasingly pay attention to questions of justice and equity [1,2], highlighting important dimensions that technoeconomic analyses, which have long dominated these debates, ignore. Mapping different justice dimensions (distributive, procedural, epistemic), as others have done, is an important first step [3][4][5].…”
Section: Introductionmentioning
confidence: 99%